Novel 4-hydroxycoumarin Derivatives Linked to N-benzyl Pyridinium Moiety as Potent Acetylcholinesterase Inhibitors: Design, Synthesis, Biological Evaluation and Docking Study - mehri abdollahi fard; Manijeh Motevalian; mohamadreza manafi; sayed-Saeid Homami (Journal of Sciences, Islamic Republic of Iran)
Based on the important interactions of donepezil with cholinesterase receptor, a series of coumarin-based N-benzyl pyridinium derivatives (5a-l) were synthesized and had in-vitro evaluation for their acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitory activities. It was revealed that compound 5l with plausible IC50 values of 0.247 µM and 1.68 µM on AChE and BuChE, respectively was the most potent anticholinesterase inhibitor compared to other synthesized compounds. The enzyme kinetic assay of compound 5l was conducted on the AChE enzyme and the compound 5l was found to be a non-competitive inhibitor of the AChE (Ki= 0.356). In addition, the compound 5l remarkably protected PC12 neurons against H2O2-induced cell death. The docking study of compound 5l revealed that the inhibitor occupied both CAS and PAS binding sites of the AChE enzyme. we have synthesized 12 products in two steps reactions and high to moderate yields. The first step involves the nucleophilic substitution reaction between 4-hydroxycoumarin and pyridyl chloride (3-pyridinium and 4-pyridinium) derivatives, which produces an intermediate of 3. Following the reaction of this intermediate with benzyl chloride derivatives, led to the synthesis of final products 5. The results were compared with donepezil and tacrine as standard drugs for AChE and BuChE inhibitory assays. Based on the IC50 values, the tendency to inhibit synthetic compounds in final products for AChE is better than BuChE. Among the products in AChE inhibitory assay, the 3-pyridinium series showed more effectiveness than the 4-pyridinium series. Docking studies and product interactions with cholinesterase receptor active sites clearly show the role of 3-pyridinium derivatives in receptor binding.